The answer is 30 I believe
Step-by-step explanation:
Inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Explanation:
As
y
=
x
+
3
x
−
2
x
y
−
2
y
=
x
+
3
or
x
y
−
x
=
2
y
+
3
or
x
(
y
−
1
)
=
2
y
+
3
or
x
=
2
y
+
3
y
−
1
Hence inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Observe that each of the function is a reflection of the other in the line
x
=
y
.
graph{(y-(x+3)/(x-2))(y-(2x+3)/(x-1))(x-y)=0 [-10, 10, -5, 5]}
Answer: 4,1 read carefully
Step-by-step explanation:
Hey there!
We have 10 pieces of paper. The probability of drawing a 10 is 1/10. Therefore, if we were to draw ten times, the ten should probably be drawn once. If we multiplied our number of drawings by four (10*4=40), our outcome of seeing our slip with the ten should also quadruple and become four times. (1*4=4)
I hope that this helps! Have an awesome day!